2019
DOI: 10.5187/jast.2019.61.2.77
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of barley to replace milk by-product in weaning pig’s diet

Abstract: The supplementation level of barley was limited because of high contents of fiber in monogastric animals. Barley contained high soluble fiber, thus it could prevent to diarrhea of weaning pigs. Moreover, as the barley break down by enzymes, free sugars come out from the barley, which could be used as an energy source in weaning pigs and replace milk by-products in weaning pig’s diet. Therefore, present study was conducted to investigate the influence of barley to replace milk by-product in weaning pig’s diet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Also, barley has relatively high fiber source which reduced diarrhea occurrence and is helpful in preventing diarrhea [ 26 ]. Also, Jin [ 7 ] demonstrated that supplement of barley in weaning pig diet reduced the incidence of diarrhea. Due to the effect of ZnO and barley, weaning pigs fed no or low milk by-product had no significant difference in diarrhea incidence compared with pigs fed high milk by-product content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, barley has relatively high fiber source which reduced diarrhea occurrence and is helpful in preventing diarrhea [ 26 ]. Also, Jin [ 7 ] demonstrated that supplement of barley in weaning pig diet reduced the incidence of diarrhea. Due to the effect of ZnO and barley, weaning pigs fed no or low milk by-product had no significant difference in diarrhea incidence compared with pigs fed high milk by-product content.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Jin [ 7 ] reported an evaluation of supplementation with barley instead of milk by-products in weaning pig’s diet. This demonstrated that barley replacing milk by-product caused low growth performance during the weaning period.…”
Section: Introductionmentioning
confidence: 99%
“…Our study did not confirm reduction of serum glucose level. Additionally, β-glucan supplementation resulted in a lower number of pathogens found in liver what can be related with reduced intestinal translocation of bacteria [52].…”
Section: Discussionmentioning
confidence: 99%
“…The papers that both assessors assessed affirmatively for all questions were included in the analysis, yielding 28 papers. These articles were Nielsen et al (2001), Houška et al (2004, Wellock et al (2008), Li et al (2008), Kutzer et al (2009), Zonderland et al (2010), Fels et al (2012, Madsen & Bee (2014), Bell et al (2015), Baldinger et al (2016), Van Wettere et al (2016, Almeida et al (2017), Vanrolleghem et al (2019, Montsho et al (2016), Kalita et al (2015), Jin et al (2019), Tsourgianis et al (2004, Devillers and Farmer (2009), Bohnenkamp et al (2013) Using Excel® software, the data regarding the impact of weaning age on piglet performance were organized for statistical analysis. The variables were tested for normality of the residuals using Shapiro-Wilk test and homogeneity of variance using Levene's test.…”
Section: Methodsmentioning
confidence: 99%